Actuator Fault Estimation and Reconfiguration Control for the Quad-Rotor Helicopter. (22nd February 2016) - Chen, Fuyang; Lei, Wen; Tao, Gang; Jiang, Bin
In this paper, an improved reconfiguration control scheme via an H∞ fault observer and adaptive control is studied for the quad-rotor helicopter with actuator faults. The bilinear problem is eliminated by constructing fault compensation and control law reconfiguration in the adaptive controller. Fault estimation is achieved by designing the fault observer with an H∞ performance index, which is applied to evaluate the 'locking in place' fault of the actuator in a quad-rotor helicopter. By drawing the H∞ performance index into the adaptive fault observer, an asymptotically convergent estimated error can be attained and the burden of the adaptive controller is alleviated. Some simulation and experimental results confirm the availability of the reconfiguration control scheme.